A study on laser-fiber coupling efficiency and ablation rate in femtosecond laser deep microdrilling - Shen, Xinwei; Bian, Qiumei; Chang, Zenghu; Lei, Shuting; Wu, Benxin (My University, 2012)
Laser microdrilling is a common micromachining operation in many industrial applications. This paper presents a new laser microdrilling technique in which a hollow-core fiber is employed to transmit femtosecond laser pulses to the target position. The coupling efficiency between the laser and the fiber is investigated and found to be strongly related to pulse energy and pulse duration. A parametric study on the ablation rate indicates that in microdrilling of a stainless steel (type 303), the operating parameters including pulse energy, pulse duration, sample thickness, focal length and sample-fiber distance can affect the ablation rate. The experimental results show that the new technique developed in this study is feasible to conduct microdrilling of holes with high aspect ratio.
Keywords: Femtosecond laser; Microdrilling; Ablation rate; Hollow-core fiber; Stainless steel